The death penalty : an historical and theological survey - Megivern, James J. (New York : Paulist Press, 1997)
Includes information on the death penalty and early Christiantity; movement in the medieval church; The Waldensian "no" and the Thomastic "yes" (Peter Waldes, Alan of Lille, St. Thomas Aquinas, and John Duns Scotus); Renaissance and Reformation dilemmas (six Renaissance popes and the spiral of violence; popes of the Tridentine Reform and the death penalty; Roman executions after the Council of Trent); post-Tridentine troubles and tribulations; englightenment (religious and secular); from Vatican I to Vatican II; the American context; and the U.S. Catholic bishops' turnaround (Catholic anti-death penalty activities proliferate).
The death penalty and early Christianity -- Movement in the medieval church -- The Waldensian no and the Thomistic yes -- Renaissance and Reformation dilemmas -- Post-Tridentine troubles and tribulations -- Enlightenment: religious and secular -- From Vatican I to Vatican II -- The American context -- The U.S. Catholic bishops' turnaround -- Consolidating consistency (1984-1990) -- New setbacks and advances (1991-1996) -- Instead of a conclusion.
Includes bibliographical references (p. 573-612) and index.
Keywords: Capital punishment -- History; Capital punishment -- Religious aspects; Capital punishment -- Moral and ethical aspects